2018
DOI: 10.1073/pnas.1722380115
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenyl esters in juvenile mountain pine beetle and sex-specific release of the aggregation pheromone trans -verbenol

Abstract: Significancetrans-Verbenol is a critical aggregation pheromone of the female mountain pine beetle. It is derived from a compound of the host defense, the monoterpene α-pinene. We found that beetles accumulate monoterpenyl esters during early life stages. These may serve as a previously unknown reservoir for the sex-specific release of aggregation pheromone when female beetles synchronize the mass colonization of a new host tree. The improved knowledge of the mountain pine beetle pheromone system can inform pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…One of the oxidised monoterpenes produced by a MPB P450 is the aggregation pheromone (−)‐ trans ‐verbenol. (−)‐ trans ‐Verbenol is derived from the pine oleoresin monoterpene (−)‐α‐pinene and accumulates in the phloem‐feeding MPB larvae in the form of monoterpenyl ester (Chiu et al ., 2018, 2019c2018, 2019b). These esters then serve as reservoir for the release of aggregation pheromone in the adult MPB.…”
Section: The Mountain Pine Beetle System: Example For Co‐evolution Ofmentioning
confidence: 99%
“…One of the oxidised monoterpenes produced by a MPB P450 is the aggregation pheromone (−)‐ trans ‐verbenol. (−)‐ trans ‐Verbenol is derived from the pine oleoresin monoterpene (−)‐α‐pinene and accumulates in the phloem‐feeding MPB larvae in the form of monoterpenyl ester (Chiu et al ., 2018, 2019c2018, 2019b). These esters then serve as reservoir for the release of aggregation pheromone in the adult MPB.…”
Section: The Mountain Pine Beetle System: Example For Co‐evolution Ofmentioning
confidence: 99%
“…Chen et al, 2016;Qiu et al, 2012;Reed et al, 1994). Specific CYPs function in the midgut and fat body of bark beetles, converting plant monoterpenes into aggregation pheromones (Chiu et al, 2018(Chiu et al, , 2019Huber et al, 2007;Nadeau et al, 2017;Sandstrom et al, 2008Sandstrom et al, , 2006. In locusts, a tissue-specific CYP transforms phenylalanine into a precursor for cyanide production (Wei et al, 2019), and in the fall webworm, Hyphantria cunea, another pheromone gland-specific CYP catalyzes the epoxidation of open chain precursors of cis-9,10-epoxy-(3Z,6Z )-3,6-henicosadiene and cis-9,10-epoxy-(3Z,6Z )-1,3,6-henicosatriene to their final cyclic forms (Rong et al, 2014).…”
Section: Biosynthetic Pathway Assembly In Gland Cell Type Evolutionmentioning
confidence: 99%
“…It was previously thought that only female MPB produce, and immediately release, trans -verbenol by oxidation of α-pinene upon landing on a new host tree 11,19 . However, we recently showed that both male and female MPB accumulate verbenol as fatty acid esters during their juvenile life stages, suggesting that formation of verbenol and verbenyl esters occurs in both sexes possibly as part of monoterpene detoxification in the feeding larvae 20 . While both sexes accumulate verbenyl esters as larvae, only females retain these metabolites when they emerge as adults from the brood tree and may use them as a source for sex-specific pheromone release 20 .…”
Section: Introductionmentioning
confidence: 98%